Susceptibility of dendritic cells from individuals with schistosomiasis to infection by Leishmania braziliensis. (January 2018) - Lopes, Diego Mota; de Almeida, Tarcísio Vila Verde S.; de Souza, Robson da Paixão; Ribeiro, Luís Eduardo Viana; Page, Brady; Fernandes, Jamille de Souza; Carvalho, Edgar M.; Cardoso, Luciana Santos
Highlights: Coinfection with leishmaniasis and schistosomiasis is associated with severe forms of cutaneous lesions. Dendritic cells from patients with schistosomiasis are more susceptible to an infection with L. braziliensis . Dendritic cells from patients with schistosomiasis has a lower degree of activation and a regulatory profile. Abstract: Coinfection with leishmaniasis and schistosomiasis has been associated with increased time to healing of cutaneous lesions of leishmaniasis. The objective of this study was to evaluate the effect of Leishmania braziliensis infection on co-cultures of monocyte-derived dendritic cells (MoDCs) with autologous lymphocytes from patients with schistosomiasis and patients with cutaneous leishmaniasis. MoDCs were differentiated from peripheral blood monocytes, isolated by magnetic beads, infected with L. braziliensis, and co-cultured with autologous lymphocytes. Expression of HLA-DR, CD1a, CD83, CD80, CD86, CD40, and the IL-10 receptor (IL-10R) on MoDCs as well as CD28, CD40L, CD25, and CTLA-4 on lymphocytes were evaluated by flow cytometry. The production of the cytokines IL-10, TNF, IL-12p40, and IFN-γ were evaluated by sandwich ELISA of the culture supernatant. The infectivity evaluation was performed by light microscopy after concentration of cells by cytospin and Giemsa staining. It was observed that the frequency of MoDCs expressing CD83, CD80, and CD86 as well as the MFI of HLA-DR were smaller in the group of patients with schistosomiasis compared to the group of patients with leishmaniasis. On the other hand, the frequency of IL-10R on MoDCs was higher in patients with schistosomiasis than in patients with leishmaniasis. CD4 + and CD8 + T lymphocytes from patients with schistosomiasis presented a lower frequency of CD28 and a higher frequency of CTLA-4 compared to lymphocytes from patients with leishmaniasis. Levels of IL-10 were higher in the supernatants of co-cultures from individuals with schistosomiasis compared to those with leishmaniasis. However, levels of TNF, IL-12p40, and IFN-γ were lower in the group of individuals with schistosomiasis. Regarding the frequency of MoDCs infected by L. braziliensis after 72 h in culture, it was observed that higher frequencies of cells from patients with schistosomiasis were infected compared to cells from patients with leishmaniasis. It was concluded that MoDCs from patients with schistosomiasis are more likely to be infected by L. braziliensis, possibly due to a lower degree of activation and a regulatory profile.